Analisis Miskonsepsi Bahan Ajar IPAS Kurikulum Merdeka pada Siswa Kelas III Sekolah Dasar - Halimah, Siti Musyarofah Nur; Rosyidah, Rosyidah; Ratnasari, Yuni; Fakhriyah, Fina (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This research aims to identify misconceptions in the science and science teaching materials for class III of the Merdeka Curriculum, which are contained in the 2022 Science and Technology Package Book from the Ministry of Education and Culture, the Free Curriculum General Elementary School Maestro Companion Book, and the Merdeka Curriculum Science 3A Learning Companion Book. The method used is descriptive qualitative with data collection through observation and documentation. Misconceptions in teaching materials are categorized into five types: Misidentifications, Overgeneralization, Oversimplifications, Obsolete Concepts and Terms, and Undergeneralization. The research results show that there are misconceptions in science teaching materials. Misidentifications were found in the Animal Breeding and Types of Metamorphosis material. Overgeneralization occurs in material on Invertebrate Animals, Life Cycles of Living Creatures, and Metamorphosis of Living Creatures. Oversimplifications are found in almost all materials, including Invertebrate and Vertebrate Animals, Form and Function of Animal Body Parts, Various Ecosystems, Symbiosis Between Living Things, and Energy Sources. No misconceptions were found in the Obsolete concepts and terms and Undergeneralization categories. This research emphasizes the importance of preparing more accurate and comprehensive teaching materials to support better student understanding